Self Helps Groups in Mizoram: A Study of Group Governance and Nature of Bank- Linkages - Laldingliana. C; Singh Bhartendu (The Indian Journal of Economics, 2023)
This paper examines the performance of self-help groups in the state of Mizoram (Northeast India) with reference to group-governance and the nature of bank-linkages. The study covered a sample of 500 SHGs drawn from all districts (08) of Mizoram. The performance of SHG was measured mainly on the basis of NABARD$1 (Bs SHG performance indicators. It was found that SHGs in Mizoram were democratically governed (high level of members participation) in terms of selection of their leaders and identification of group activities. It attained a medium level of performance with respect to management of group lending system and access to formal bank credit. However, SHGs in Mizoram were found lagged in terms of regularity of meetings and savings, which could be one of the important backlogs that need to be improved for the sustainability of the movement. Meanwhile, Mizoram Rural Bank (MRB) has made a significant contribution to the SHG movement, registering over 93 percent of the total selected SHGs in Mizoram.s
Keywords: NABARAD's SHG perfomance indicators; NABARD; Performance Mizoram; Self-help groups; Chi-Square Statistics